Slang, Accents, and Dialects: The Ever-Changing Landscape of English - Ibrohimova Farzona Firdavszoda; Shamsiddinova Dilafruz (Periodica Journal, 2025)
The English language is constantly evolving, shaped by cultural shifts, technological advancements, and gloabal influences. Slang, accents, and dialects play a crucial role in this transformation, reflecting regional identities, social trends, and linguistic creativity. This article explores how slang develops and spreads, how accents shape perceptions of identity and communication, and how dialects preserve cultural heritage while adapting to modern influences. Additionally, the impact of digital communication and globalization on these linguistic variations is examined. By understanding these elements, we gain insight into the dynamic and ever-changing nature of the English language
Keywords: Dialects; Communication